Coastal Structures 2003 2004
DOI: 10.1061/40733(147)75
|View full text |Cite
|
Sign up to set email alerts
|

NEES Multidirectional Wave Basin for Tsunami Research

Abstract: Oregon State is upgrading its multidirectional wave basin under the National Science Foundation Network for Earthquake Engineering Simulation (NEES) program to create a next-generation experimental testing facility for research and practicing engineers. The new facility addresses the unique requirements posed by tsunami researchers, with basin dimensions and wave generation capabilities closely matching the community's vision of the "ideal basin". When completed in 2004, the basin will support high resolution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It was found that the impulsive load is a function of wave characteristics. For obtaining the wave force, the relationship of Goda (Yim, 2005) was used which considers the slowing of tsunami force. Shoji, Hiraki (Luo et al , 2013) performed experiments and the tsunami wave pressed in their experiments were higher than predictions of Goda (Yim, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the impulsive load is a function of wave characteristics. For obtaining the wave force, the relationship of Goda (Yim, 2005) was used which considers the slowing of tsunami force. Shoji, Hiraki (Luo et al , 2013) performed experiments and the tsunami wave pressed in their experiments were higher than predictions of Goda (Yim, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For obtaining the wave force, the relationship of Goda (Yim, 2005) was used which considers the slowing of tsunami force. Shoji, Hiraki (Luo et al , 2013) performed experiments and the tsunami wave pressed in their experiments were higher than predictions of Goda (Yim, 2005). Iemura, Pradono (Fukui et al , 1963) carried out hydraulic tests of tsunami waves in a wave flume for considering the effect of breakwaters and debris for dry bridges located in land.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation